High Genetic Variation in Y Chromosome Patterns of the Mocoví Population - Glesmann, Laura Ángela (2011)
In numerically small ethnic groups, the loss of genetic variability in the Y chromosome is frequent, because this genomic compartment is often subjected to selective sweeps. Despite its small size, the Mocoví population retains a significant amount of genetic variation in relation to other native communities, but their Y chromosome diversity is not known in depth. The aim of this study was to analyze the genetic variability of the Y chromosome in a sample of Mocoví males from Santa Fe province (Argentina). We genotyped 11 short tandem repeats (STRs) and two single nucleotide polymorphisms (SNPs): M3 and M346. The diversity observed was high, and the 25 haplotypes obtained were compared to the YHRD database, with 13 of them absent of that database. A comparison with previous data reported from other Gran Chaco native groups showed significant differences between the Mocoví and other populations of different ethnic origin. This result and other studies on molecular markers of the Mocoví prove that this ethnic group retains a high genetic diversity that clearly differentiate them from other Amerindian populations.